A statistical comparison of contact angle measurement methods. Issue 16 (18th August 2019) - Kirk, Seth; Strobel, Mark; Lyons, Christopher S.; Janis, Stuart
Abstract: Contact angles are the characteristic angles made between the surface of a liquid and a solid surface. The measurement of contact angles can be done with multiple methods. However, because there are no reference standards for contact angle measurements, it is difficult to estimate the accuracy of a contact angle measurement method. It is possible to use statistical estimations of the precision and sensitivity of contact angle measurement methods and from this analysis to identify a preferred method. Contact angle measurements made using the Wilhelmy-plate method, a goniometer method, a tilting-plate method, and two automated drop dispensing and imaging methods are compared. Statistical analyses show that the Wilhelmy-plate method provides measurements with the greatest precision and sensitivity and is therefore a preferred contact angle measurement method.